Concerns of anophthalmic patients-a comparison between cryolite glass and polymethyl methacrylate prosthetic eye wearers - Rokohl, Alexander C.; Koch, Konrad R.; Adler, Werner; Trester, Marc; Trester, Wolfgang; Pine, Nicola S.; Pine, Keith R.; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: To compare the concerns of experienced cryolite glass and (poly)methyl methacrylate (PMMA) prosthetic eye wearers. METHODS: One hundred six experienced cryolite glass and 63 experienced PMMA prosthetic eye wearers completed an anonymous questionnaire regarding general and specific prosthetic eye concerns at least 2 years after natural eye loss. From these independent anophthalmic populations, we identified 34 case-control pairs matched for the known influencing demographic variables of gender, occupation, age, and time since natural eye loss. RESULTS: The levels of concern were significantly lower in the cryolite glass group than those in the PMMA group for the following: loss of balance (p < 0.001), phantom sight vision (p < 0.001), pain (p < 0.001), receiving good advice (p = 0.001), fullness of orbit (p = 0.001), size (p = 0.007), direction of gaze relative to the healthy fellow eye (p = 0.005), eye lid contour (p = 0.037), comfort of the prosthetic eye (p < 0.001), colour relative to the healthy fellow eye (p < 0.001), and retention of the prosthetic eye (p < 0.001). Concerns about watering, crusting, discharge, visual perception, appearance, movement of the prosthetic eye, and health of the remaining eye were not significantly different between both groups. CONCLUSIONS: The results of this study showed that many general and specific levels of concern were significantly lower for cryolite glass prosthetic eye wearers than for PMMA prosthetic eye wearers. The question of why there are significant differences and to what extent the material of the prosthesis (cryolite glass or PMMA) has an impact on various concerns remains unanswered and should be addressed in a prospective comparative multicentre trial.
EVALuna2:35673